AN ANALYSIS OF FIGURATIVE LANGUAGE FOUND IN TWENTY ONE PILOTS SONG LYRICS - Napa, Irenius; Sulatra, I Komang; Scholastika, I Made Perdana (Journal of Humanities, Social Science, Public Administration and Management (HUSOCPUMENT), 2023)
This study intended to analyze figurative language found in the song lyrics of Scaled and Icy album by Twenty One Pilots. The objectives of this research are find out types of figurative language and analyze their meanings as found in the song lyrics of Scaled and Icy album by Twenty One Pilots. There were two theories used in this research, such as; the first theory proposed by Knickerbocker and Reninger (1974) was used to find out of figurative language used in the song lyrics of Scaled and Icy album by Twenty One Pilots, and the second theory proposed by Leech (1981) was used to analyze the meaning of figurative language found in song lyrics of Scaled and Icy album by Twenty One Pilots. The method used in collecting the data was observation method. The data were collected by browsing and downloading song lyrics from internet, reading and understanding the song lyrics, and taking note and classifying the lyrics that contain of figurative language. The collected data were analyzed descriptively by using qualitative method. After analyzing the song lyrics, this study found eight types of figurative language used in Scaled and Icy album by Twenty One Pilots. There were eight types of figurative language used in the song lyrics by Twenty One Pilots, they were 2 of simile (9%), 2 of metaphor (9%), 4 of synecdoche (18%), 1 of metonymy (4,5%), 8 of hyperbole (37%), 2 of irony (9%), 1 of paradox (4,5%), and 2 of allusion (9%). There were three of meanings found from seven types of meanings, they were connotative meaning, affective meaning, and reflected meaning.